2008
DOI: 10.1063/1.2956740
|View full text |Cite
|
Sign up to set email alerts
|

IUPAC-NIST Solubility Data Series. 87. Rare Earth Metal Chlorides in Water and Aqueous Systems. Part 1. Scandium Group (Sc, Y, La)

Abstract: This volume presents solubility data for rare earth metal chlorides in water and in ternary and quaternary aqueous systems. The material is divided into three parts: scandium group (Sc, Y, La), light lanthanide (Ce-Eu), and heavy lanthanide (Gd-Lu) chlorides; this part covers the scandium group. Compilations of all available experimental data are introduced for each rare earth metal chloride with a corresponding critical evaluation. Every such evaluation contains a tabulated collection of all solubility result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…An extensive review of the solubility data for REE chlorides has been reported in Mioduski et al (2008Mioduski et al ( , 2009aMioduski et al ( , 2009b. However, the high solubility of these compounds makes it difficult to derive standard thermodynamic properties, since a reliable thermodynamic description of solutions having multi-molar concentrations of REECl 3 requires a reliable activity model for the corresponding electrolyte.…”
Section: Ree Halogenides (Chlorides and Fluorides)mentioning
confidence: 95%
“…An extensive review of the solubility data for REE chlorides has been reported in Mioduski et al (2008Mioduski et al ( , 2009aMioduski et al ( , 2009b. However, the high solubility of these compounds makes it difficult to derive standard thermodynamic properties, since a reliable thermodynamic description of solutions having multi-molar concentrations of REECl 3 requires a reliable activity model for the corresponding electrolyte.…”
Section: Ree Halogenides (Chlorides and Fluorides)mentioning
confidence: 95%
“…They are also soluble in ethanol, acetone, and dimethyl sulfoxide (DMSO) but insoluble in dichloromethane and chloroform. The solubilities of rareearth tetracyanidoborates in water are considerably higher than those of rare-earth phosphates [71] and carbonates [72] but much lower than those of rare-earth-metal chlorides [37] and sulfates. [73] Compared with those of tetracyanidoborates of other metal cations, the water solubilities of most of the alkali-metal tetracyanidoborates [8] and of the divalent metals Zn and Cu [12] are higher than those of the rare-earth-metal tetracyanidoborates.…”
Section: Solubilitymentioning
confidence: 98%
“…For comparison, Fig. 1 also contains the recommended values of the solubility of rare earth metal chlorides at 298.2 K [ 1 3 ]. These values are precisely known within ±0.1%, and therefore they may be used as the reference data basis.…”
Section: Solubility Data For Rare Earth Metal Bromides and Iodides Inmentioning
confidence: 99%
“…This is a brief assessment which is a continuation of the critical evaluation of solubilities of rare earth metal halides in water-containing systems. The part on solubilities of chlorides was already published [ 1 3 ]. It would seem that bromides and iodides of rare earth metals are less significant than chlorides.…”
Section: Introductionmentioning
confidence: 99%